The morphology and biology of Anomala vetula Wied : an arthropod pest of turf in South Africa - Bradford, B (Rhodes University, Faculty of Science, Department of Zoology, 1946)
From Introduction: For the past eight years, the Zoology Department of Rhodes University College, in co-operation with African Explosives & Chemical Industries Ltd., has been studying certain entomological problems relating to turf on the golf course along the coastal belt of the Eastern Cape Province. The position is briefly as follows:- On the golf courses at Mossel Bay, Humewood (Port Elizabeth), Port Alfred and East London, vast damage has been done to the greens and fairways by "white grubs", the larval stages of Scarabaeidae. It would appear that these beetles had been present in the environs of the courses for many years, but it was only when large areas of the natural veld were converted into fairways, with a more or less uniform cover of grass, with Cynodon dactylon Pers. predominating, that conditions were inadvertently created which favoured the development of the beetles. It was not long after the establishment of these golf courses, that the beetles assumed the proportions of a pest, and the larvae began destroying the root system of the grasses covering the greens and fairways.
Keywords: Anomala